Shelley's Quest for Love: Queering Epipsychidion - Shih, Terence H. W. (Romanticism on the Net)

(untitled) (Université de Montréal, 2019)
This paper employs the concept of queer to examine Percy Bysshe Shelley's Epipsychidion. Shelley's idealism towards love was widely received in atheism, materialism and Platonism. Compared with other Romantic poets, Shelley exercised his concept of love very differently. Shelley's quest for love is particularly discussed in most of his love poems. Among them Epipsychidion is a long poem that Shelley wrote to demonstrate his philosophy of love. In his later life, Shelley worked on translating Plato's philosophy, particularly The Symposium, which partly focuses on Greek love, and further pondered on his own sexuality. Shelley started to draw on atheistic materialism and Platonic metaphysics. Epipsychidion extends Shelley's early concept of love, namely "a soul within our soul," and dramatizes his narrator's love towards a female character named Emily. Different from major perspectives from Shelley critics (Notopoulos, Wasserman, Sperry, Peterfreud) who particularly pay attention to Shelley's love affairs, heterosexuality, as well as the real identity of Emily in Epipsychidion, the paper instead focuses on this poem to testify Shelley's homosexuality. The closeted poet honestly, but vaguely, discloses his traumatic love towards his male "Emily" and eventually his potential suicide with the man. I argue that a queer reading of Shelley's poetry helps to reexamine Shelley's philosophy of love in Epipsychidion.